"Only Going to Get Worse": Narrative Magnifications and Emotion Work among Rural Frontline Responders in the Opioid Epidemic. Issue 4 (30th December 2020) - Vaccaro, Christian; Swauger, Melissa; Niccolai, Ashley; Morrison, Shayna; Heckert, Alex; Garcia, Victor; Lauber, Erick
Abstract : The study of narrative sociology can be used to understand how rural first responders magnify aspects of their collective stories about the opioid crisis to deflect emotional frustrations they experience. Based on 31 interviews with frontline responders in four rural counties in Appalachia, we find that responders portray themselves as capable protagonists up against hamstringing policies, opioid using clients as "their worst, " and their management of crises as a Sisyphean task. In constructing stories in this way, rural frontline responders temper frustration, and consequently sympathy, that contributes to a unique logic of care and control. This storytelling protects responders against traumas from their efforts, yet likely impedes trusting relationships with clients. A video abstract is available at https://youtu.be/lh8OkGSEsUo.